Design Simulation of Filing Sequence and Solidification Time for Cast Metal Matrix Composite by Low Pressure Die Casting - Taufik, Roni Sahroni; Tajul Ariffin, Abdullah (Praise Worthy Prize, Italy, 2011)
This research presents the design simulation of aluminum silicon carbide by Low Pressure Die Casting (LPDC). The theoretical formulation was presented for determining the filling sequence and solidification time. The simulation is presented in order to study the velocity and temperature patterns by applying sensor to the mould and cavity. As a result, an application of A356 aluminum alloy was used as a matrix material and silicon carbide was added as reinforcement particles in designing of automotive wheel were presented.